Perbedaan Penurunan Fungsi Kognitif pada Pasien Stroke Iskemik Lesi Hemisfer Kanan dan Kiri Di RSUD Dr. Moewardi - Sitaresmi, Adya; Widjojo, FX Soetedjo; Ghozali, Dhoni Akbar (Nexus Kedokteran Klinik, 2014)
Background: Stroke is a major health problem in many parts of the world and is increasing in prevalence in line with modernization. Damage to brain cells after stroke cause cognitive function disability that affect the quality of life and independence of the patient. Decline in cognitive function relates to size and location of the lesion. This research aims to find out the differences in cognitive function loss between right and left hemisphere ischemic stroke patients. Methods: This research is observational analytic study with retrospective cohort design performed in an Outpatient Neurology Clinic at RSUD Dr. Moewardi. There are 30 patients as subject consists of 14 right hemisphere and 16 left hemisphere ischemic stroke patients. Sampling techniques is exhaustive sampling. Cognitive function of patients with ischemic stroke was measured using Indonesian version of MoCA (Montreal Cognitive Assessment) questionnaires. The data collected are presented in tabular form and analyzed using the multiple linear regression analysis through SPSS 20.00 program for Windows. Results: The location of lesions influence cognitive function score significantly (p = 0,027) and there is a difference in which patients with left hemisphere lesion score lower cognitive function than patients with right hemisphere lesion with regression coefficient (β =-4.604). Age is a confounding variable on the relationship between lesion location with cognitive function. Age has negative effect on cognitive function, where the increase of age correlates with the declining cognitive function (p = 0.040; β = 0.228-). Conclusions: The decline of cognitive function in left hemisphere ischemic stroke patients is more severe than right hemisphere ischemic stroke patients. Keywords: Cognitive Function Decline, Right Hemisphere Ischemic Stroke, Left Hemisphere Ischemic Stroke